2021
DOI: 10.4018/ijeis.2021010107
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Emotion and Cognition in Information System

Abstract: The current research on the information systems (IS) shows that emotion and cognition can affect behavior, but their interaction with each other is not clear. This paper attempts to clarify the interaction between emotion and cognition and explain their antecedents and consequences. This research includes a meta-analysis composed of 33 papers related to emotion and cognition in high-quality IS journals. Results reveal cognition affects emotion when emotion can be changed or manipulated by an external stimulus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The American newspapers highlight the emotion of fear when reporting the Hong Kong issues, which is consistent with the research results of Ming and Ma (2022: 37). News reporting is the cognitive processing of information, and the existence of emotions can precede cognition (Shiau et al, 2021: 132). Therefore, the emotions toward China’s government can affect the cognitive perspectives of newspapers on China’s problems, that is, emotions affect the ways by which newspapers perceive the world, and these emotions are dominated by the ideologies of the community in which newspapers exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The American newspapers highlight the emotion of fear when reporting the Hong Kong issues, which is consistent with the research results of Ming and Ma (2022: 37). News reporting is the cognitive processing of information, and the existence of emotions can precede cognition (Shiau et al, 2021: 132). Therefore, the emotions toward China’s government can affect the cognitive perspectives of newspapers on China’s problems, that is, emotions affect the ways by which newspapers perceive the world, and these emotions are dominated by the ideologies of the community in which newspapers exist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the emotions toward China’s government can affect the cognitive perspectives of newspapers on China’s problems, that is, emotions affect the ways by which newspapers perceive the world, and these emotions are dominated by the ideologies of the community in which newspapers exist. Meanwhile, cognitive frameworks can also act on emotions (Shiau et al, 2021: 125). For example, the negative news reports on Hong Kong National Security Law in American newspapers will affect some people’s emotions toward China, who do not know much about Chinese culture and society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It builds up the relationship between outside stimulus and an individual’s response, which is manifested as a specific attitude or behavior change ( Conner and Armitage, 1998 ). Shiau et al (2021) revealed that cognitive and affective experiences have a positive impact on behavioral intention. In terms of cognition, Lemon and Verhoef (2016) attempted to combine consumer experience with behavior in terms of consumer satisfaction and service quality and found that consumer experience has a positive impact on behavioral intention.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%